Resultados da Angioplastia Primária num Centro de Referência. Evolução Intra-Hospitalar - Ramos, R (2009)
INTRODUCTION: Primary angioplasty is accepted as the preferred treatment for acute myocardial infarction in the first 12 hours. However, outcomes depend to a large extent on the volume of activity and experience of the center. Continuous monitoring of methods and results obtained is therefore crucial to quality control. OBJECTIVE: To describe the demographic, clinical and angiographic characteristics as well as in-hospital outcomes of patients undergoing primary PCI in a high-volume Portuguese center. We also aimed to identify variables associated with in-hospital mortality in this population. METHODS: This was a retrospective registry of consecutive primary PCIs performed at Santa Marta Hospital between January 2001 and August 2007. Demographic, clinical, and angiographic characteristics and in-hospital outcomes were analyzed. Independent predictors of in-hospital mortality were identified by multivariate logistic regression analysis. RESULTS: A total of 1157 patients were identified, mean age 61+/-12 years, 76% male. Mean pain-to-balloon time was 7.6 hours and primary angiographic success was 88%. Overall in-hospital mortality was 6.9%, or 5.5% if patients presenting in cardiogenic shock were excluded from the analysis. Previous history of heart failure, cardiogenic shock on admission, invasive ventilatory support, major hemorrhage, and age over 75 years were found to be associated with increased risk of in-hospital death. Conclusions: In this center primary PCI is effective and safe. Angiographic success rates and in-hospital mortality and morbidity are similar to other international registries. Patients at increased risk for adverse outcome can be identified by simple clinical characteristics such as advanced age, cardiogenic shock on admission, mechanical ventilation and major hemorrhage during hospitalization.